The Role of Pericytes in Ischemic Stroke: Fom Cellular Functions to Therapeutic Targets - Zhou, Sheng-Yu; Guo, Zhen-Ni; Zhang, Dian-Hui; Qu, Yang; Jin, Hang (Frontiers in Molecular Neuroscience, 2022)
Ischemic stroke (IS) is a cerebrovascular disease causing high rates of disability and fatality. In recent years, the concept of the neurovascular unit (NVU) has been accepted by an increasing number of researchers and is expected to become a new paradigm for exploring the pathogenesis and treatment of IS. NVUs are composed of neurons, endothelial cells, pericytes, astrocytes, microglia, and the extracellular matrix. As an important part of the NVU, pericytes provide support for other cellular components and perform a variety of functions, including participating in the maintenance of the normal physiological function of the blood-brain barrier, regulating blood flow, and playing a role in inflammation, angiogenesis, and neurogenesis. Therefore, treatment strategies targeting pericyte functions, regulating pericyte epigenetics, and transplanting pericytes warrant exploration. In this review, we describe the reactions of pericytes after IS, summarize the potential therapeutic targets and strategies targeting pericytes for IS, and provide new treatment ideas for ischemic stroke.